ANALISIS KESULITAN BELAJAR MATEMATIKA PADA PESERTA DIDIK TUNARUNGU KELAS II DI UPT SPF SD NEGERI MANNURUKI - Cahyani, Regita; Husniati, Andi; Ardillah Wahyudi, Andi (Almeera Education, 2024)
This research employs a qualitative approach with a case study design to investigate the challenges faced by second-grade deaf students in learning mathematics at UPT SPF SD Negeri Mannuruki, as well as the underlying causes of these difficulties. The subject of this study is a single deaf student in the second grade at UPT SPF SD Negeri Mannuruki. Data collection methods include observation and interviews. The findings indicate that the student encounters several difficulties in solving mathematical word problems, specifically: 1) Difficulty in understanding concepts; 2) Difficulty in grasping principles; and 3) Difficulty in comprehending verbal problems. The internal factors contributing to these difficulties include the student's interest in mathematics, study habits related to mathematics, and motivation to learn the subject. External factors encompass influences from the family and school environments.